DEVELOPMENT OF THE WORLD MARKET OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Khomutenko, Lyudmila; Panchenko, Vitalii (Socio-economic relations in the digital society, 2023)
This article examines the development of information and communication technologies (ICT), which consist of information and communication tools for the collection, processing and transmission of data. The peculiarities and structure of the ICT market are studied, as well as the current trends in the development of the industry are analyzed. The article also presents the amount of ICT spending in the world and strategic technological trends. The author analyzed the change in the structure of international production, the trends of ICT management and the results of the analysis of the ICT market in different countries of the world. The market of information and communication technologies of Ukraine is analyzed from the point of view of its development, taking into account macroeconomic indicators and market interaction. Recommendations are given for the further development of the ICT market in Ukraine, taking into account the strategic directions of the development of the information society.